2020
DOI: 10.1177/0081246320956419
|View full text |Cite
|
Sign up to set email alerts
|

De/coloniality, disabled sexualities, and anti-oppressive education: a review of Southern African literature

Abstract: This review seeks to establish the current body of knowledge on the intersection of de/coloniality and the sexuality of disabled individuals. It suggests that few studies problematise the lack of such intersections in Southern Africa. The review locates this dearth of knowledge within the recent rollout of comprehensive sexuality education in schools, which remains silent to intersections of de/coloniality, disability, and sexuality. This analysis builds on the recommendation of Kumashiro to consider marginali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Within the study, Ubisi [13] suggested interrogating discourses of who should be allowed to reproduce (or not), and with whom, which is largely missing in most sexuality education for youth living with disabilities. On the other hand, Ubisi [15] suggested emancipating the sexuality of disabled persons by integrating themes of decoloniality, disability and sexuality within anti-oppressive education like the CSE SLPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the study, Ubisi [13] suggested interrogating discourses of who should be allowed to reproduce (or not), and with whom, which is largely missing in most sexuality education for youth living with disabilities. On the other hand, Ubisi [15] suggested emancipating the sexuality of disabled persons by integrating themes of decoloniality, disability and sexuality within anti-oppressive education like the CSE SLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Ubisi [13] also proposed post-structural theory such as Foucault's governmentality and Butler's performativity theory to unearth underlying discourses behind socio-medical and cultural discourses about the sexuality of persons living with disabilities, such as who should be allowed to reproduce (and with whom). I have further suggested decoloniality theory as an emancipatory framework to unmask how colonial standards have affected how we view the health and fertility of persons living with disabilities in other work [15]. To date, few studies have considered this knowledge to examine the visibility of the sexuality of persons living with disabilities in South Africa's Department of Basic Education's CSE SLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Like the figure of diffraction below (Figure 2), as the marks of colonisation materialise with ongoing iterations of relations, the spectres of colonisation re-emerge as multiplicitous colonialities and the possibilities they exclude; that is, interference patterns. Entangled with the materialisation of various colonialities, such as those of gender (Lugones, 2007), ableism (Ubisi, 2021), and class (Quijano, 2000), the multiplicitous im/possibilities of becoming otherwise always already exist. The configuration that operates to exclude other ways of being simultaneously defines the parameters for being otherwise.…”
Section: Childhoods As Diffractive Colonialitiesmentioning
confidence: 99%